Project “The Wooden Treasure. Preserving Heritage Design Future” – 3D visualization as a form of monument's protection - Kowalczyk, Paulina; Kowalski, Łukasz; Pietrasiewicz, Tomasz; Przystojecki, Tadeusz; Zętar, Joanna (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
The region of Lublin has a rich tradition of the usage of timber in construction. A few dozen years ago wood was still the predominant building material in villages, towns and on the outskirts of big cities. Small multicultural towns were a characteristic element of the cultural landscape of the region. The wooden buildings of these towns compose one of the most unique phenomena in Polish and architecture. To this day some examples of particular small towns’ buildings were preserved. The main aim of the project is to create digital 3D reconstructions of five small towns of the Lublin region and a model illustrating wooden architecture of the Norwegian town of Larvik in different historical periods. All models will be accesible online on multimedia service dedicated to wooden architecture and methods of its conservation and will have connection with inventory of the most representative monuments of wooden architecture of the Lublin region, uploaded and shared via the Internet.